Investigate the relationship between Storm Formation and Tropical Cyclone Genesis Potential Index in the Vietnam East Sea - Linh, Nguyen Manh; Katzfey, Jack; McGregor, John; Chi, Nguyen Kim; Nam, Pham Quang; Duc, Tran Quang; Ha, Pham Thanh; Huy, Hoang Danh; Hiep, Nguyen Van; Van Tan, Phan (VNU Journal of Science: Earth and Environmental Sciences, 2019)
Abstract: In this paper, the relationship between Tropical Cyclone (TC) Genesis Potential Index (GPI) and the number of TC (NTC) associated with ENSO over the Vietnam East Sea (VES) was investigated. Observed TC data of the Regional Specialized Meteorological Center (RSMC) Tokyo Typhoon Center and ERA Interim reanalysis data for the period 1985-2015 were used. The results show a good agreement between GPI and NTC over the VES with the correlation coefficient is 0.84. There were more TCs formed over the VES during La Nina years and less TCs during El Nino years. There were positive anomalies of GPI, environmental factors (relative humidity, sea surface temperature, absolute vorticity, potential intensity)over the region where the highest densityof TCs genesis locatedduring La Nina years while there were negative anomalies found during El Nino years. Relative humidity has the largest contribution to the positive difference GPI between La Nina years and El Nino years, the less contribution comes from the potential intensity, absolute vorticity, and wind shear. Keywords: GPI, Tropical Cyclone Genesis, ENSO, Vietnam East Sea. References : [1] K.A. Emanuel, D.S. Nolan, Tropical cyclone activity and global climate, Reprints, 26th Conference on hurricane and Tropical Meteorology, American meteorological Society: Miami, (2004) 240–241. [2] D.S. Nolan, E.D. Rappin, K.A. Emanuel., Tropical cyclogenesis sensitivity to environmental parameters in radiative-convective equilibrium, Quarterly Journal of the Royal Meteorological Society. 133 (2007) 2085–2107. [3] S.J. Camargo, K.A. Emanuel, A.H. Sobel, Use of the Genesis Potential Index to Diagnose ENSO effected on Tropical Cyclone Genesis, American Meteorological Society.20 (2007) 4819-4834 [4] C.L. Bruyere, G.J. Holland, E. Towler, Investigating the Used of a Genesis Potential Index for Tropical Cyclones in the North Atlatic Basin, American Meteorological Society..25 (2012) 8611-8626 [5] Song Yuan, Wang Lei, Lei Xiaoyan and Wang Xidong, Tropical cyclone genesis potential index over western north Pacific simulated by CMIP5 models, (2015). [6] Lei Wang, Diagnostic of the ENSO modulation of Tropical cyclogenesis over the southern South China Sea using a genesis potential index, Acta Oceanol. Sin., Vol. 31, No. 5 (2012) 54-68. [7] Xin Kieu-Thi, Hang Vu-Thanh, Truong Nguyen-Minh, Duc Le, Linh Nguyen-Manh, Izuru Takayabu, Hidetaka Sasaki, Akio Kito, Rainfall and tropical cyclone activity over Vietnam simulated and projected by the Non-Hydrostatic Regional Climate Model – NHRCM, Journal of the Meteorological Society of Japan. 94A (2016) 135-150. [8] https://www.jma.go.jp/jma/jma-eng/jma-center/ rsmc-hp-pub-eg/trackarchives.html [9] Trần Quang Đức, Xu thế biến động của một số đặc trưng ENSO, Tạp chí Khoa học Đại học Quốc gia Hà Nội, Khoa học Tự nhiên và Công nghệ. 1S (2011) 29-36. [10] https://origin.cpc.ncep.noaa.gov/products/analysis_monitoring/ensostuff/ONI_v5.php [11] E. Palmen, Formation and development of tropical cyclones, Proceedings of tropical cyclone Symposium, Brisbane, Australian Bur. Meteorol., Melbourne, (1956) 213-231 [12] M. DeMaria, The effect of vertical wind shear on tropical cyclone intensity change, Jounal of Atmospheric Sicences. 53 (1996) 2076-2087. [13] S.J. Camargo, Diagnosis of the MJO modulation of Tropical cyclogenesis using an empirical index. American Meteorological Society. 66 (2009) 3061-3074. [14] S.J. Camargo, A.H. Sobel, Anthony G. Barnston, K.A. Emanuel, Tropical cyclone genesis potential index in climate models, Tellus A: Dynamic Meteorology and Ocenaography. 59:4 (2007) 428-443. doi: 10.1111/j.1600-0870.2007. 00238.